PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN BRAND PANAMA PADA SUMMARECON MALL SERPONG DI TANGERANG - Juliansyah, Tria; Mustakim, Masran (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of Price and Product Quality on Consumer Satisfaction of Panama Brand at Sumareccon Mall Serpong in Tangerang. The method used is a quantitative method with an associative type. The sampling technique used is Probability Sampling with Random Sampling type. The number of samples used in this research was 96 respondents. Data analysis techniques using instrument testing, namely validity testing and reliability testing. Classic assumption tests are normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test and hypothesis tests namely t test and F test. The results of this research are that price has a significant effect on consumer satisfaction with a simple linear regression equation Y= 14.941 + 0.555 X1. Hypothesis testing obtained a value of tcount>ttable (7.292>1.986). Product Quality has a significant effect on Consumer Satisfaction with the simple linear regression equation Y= 13.121 + 0.580 X2. Product Price and Quality have a positive and significant effect on Consumer Satisfaction with the multiple regression equation, namely Y = 8.777 + 0.376X1 + 0.356 X2. Hypothesis testing obtained a value of Fcount > Ftable (37.891 > 3.094). Thus it can be concluded that Product Price and Quality have a positive and significant effect on Consumer Satisfaction.